2000
DOI: 10.1046/j.1440-1681.2000.03382.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Metabolism In Cyclosporine A‐Treated Rats: Dose‐ And Time‐Related Changes In Liver And Kidney

Abstract: 1. We investigated the simultaneous effects of cyclosporine A (CsA) treatment in rats on glutathione metabolism, oxidative status and their interorgan relationship in the liver and kidney. 2. Reduced and oxidized glutathione (GSH and GSSG, respectively), lipid peroxidation and the activity of several enzymes of the glutathione cycle were evaluated in adult Wistar rats treated daily (i.p.) with saline, CsA vehicle (olive oil) or CsA (10 and 20mg/kg per day) for either 1 or 4 weeks (short- and long-term treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…Furthermore, TGFβ-mediated EMT changes could be inhibited by direct antioxidants such as NAC and catalase in rat renal tubular epithelial cells and alveolar epithelial cells [37, 38]. CsA is known to increase ROS levels in two ways: i) CsA treatment itself can reduce levels of components of the antioxidant defense system, thereby enhancing ROS levels in the kidney, and ii) CsA-mediated production of TGFβ and angiotensin II can further enhance the level of ROS by activating NADPH oxidase [6, 7, 39]. These results imply that oxidative stress might be one of EMT-promoting factors in CsA-fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TGFβ-mediated EMT changes could be inhibited by direct antioxidants such as NAC and catalase in rat renal tubular epithelial cells and alveolar epithelial cells [37, 38]. CsA is known to increase ROS levels in two ways: i) CsA treatment itself can reduce levels of components of the antioxidant defense system, thereby enhancing ROS levels in the kidney, and ii) CsA-mediated production of TGFβ and angiotensin II can further enhance the level of ROS by activating NADPH oxidase [6, 7, 39]. These results imply that oxidative stress might be one of EMT-promoting factors in CsA-fibrosis model.…”
Section: Discussionmentioning
confidence: 99%
“…The decreases observed in sleep-deprived rats are about as low as can be found in other experimental models of disease. For example, toxicity due to chronic cyclosporine A administration is associated with a 30 -37% decrease in rat liver glutathione (33,47). Starvation for 72 h or streptozotocin-induced diabetes in rats are each associated with 25% decreases in liver glutathione (43,67), whereas skin scald injury-induced organ damage is associated with a 50% decrease (54).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was reported that the GSSG level increases in plasma, lung and brain, 56 liver, 56,62 and kidney. 60 Thus, the results obtained here, for each biomarker in postintoxication samples, can be considered as a consequence of exposure to lead. Exposure to Pb causes multiple pathologies including renal 10 dysfunction, triggering oxidative stress, and at the same time the stimulation of the antioxidant defense mechanism, increasing the secretion of GSH which protects ROS cells and generates GSSG as a product that is considered as a metabolite marker of cellular damage.…”
Section: ■ Results and Discussionmentioning
confidence: 84%